Renal recovery following orthotopic liver transplant after prolonged kidney injury: Perspectives on diagnosing hepatorenal syndrome and determining which patients should undergo simultaneous liver kidney transplantation - Mary Elizabeth Card; Gilbert Moeckel; Jeffrey Michael Turner (Journal of Renal and Hepatic Disorders)
We present a case of an individual with cirrhosis and renal failure. This case is notable because the patient was found to have hepatorenal syndrome (HRS) superimposed on Immunoglobulin A (IgA) nephropathy. After 8 months of dialysis, the patient had significant renal recovery following orthotopic liver transplant (OLT). Cases such as this are not likely to be rare, as case series have shown that IgA deposits are a common occurrence in patients with cirrhosis, including those who have HRS. While current diagnostic criteria for HRS emphasize the importance of excluding glomerular lesions, we argue that this approach should be reconsidered. More specifically, we feel that the diagnostic approach to HRS should be more inclusive of cases in which patients have simultaneous HRS and glomerular injury. In addition, our case highlights the challenges in determining which patients will benefit most from simultaneous liver–kidney transplants over OLTs alone.